The effect of e-modules on physics learning in senior high school: A meta-analysis - Fadillah, Muhammad Aizri; Asrizal, Asrizal; Festiyed, Festiyed; Usmeldi, Usmeldi (Indonesian Journal of Science and Mathematics Education, 2024)
This study aims to investigate the impact of using e-modules in physics education on senior high school through a meta-analysis. The method used is quantitative meta-analysis to evaluate the effectiveness of e-modules in the context of physics learning. Out of 995 papers screened, 15 articles were selected for further analysis. The results show that e-modules are significantly more effective than traditional learning, with an effect size of d = 18.45, Z = 5.79 (P < 0.00001). Subgroup analysis revealed that the effectiveness of e-modules varies based on learning dimensions, teaching models, and the physics topics being taught. Thus, e-modules significantly positively impact various aspects of student learning, including creative thinking, critical thinking, learning outcomes, science process skills, conceptual understanding, and science literacy. This study highlights the potential of e-modules to enhance physics learning. However, some data limitations exist in certain dimensions, such as creative thinking, science process skills, conceptual understanding, and science literacy.